Porous loofah-sponge-like ternary heterojunction g-C3N4/Bi2WO6/MoS2 for highly efficient photocatalytic degradation of sulfamethoxazole under visible-light irradiation. (September 2021) - Liang, Huanjing; Guo, Jiaying; Yu, Mingchuan; Zhou, Yufei; Zhan, Ruonan; Liu, Cong; Niu, Junfeng
Abstract: A novel porous loofah-sponge-like ternary heterojunction g-C3 N4 /Bi2 WO6 /MoS2 (CN-BM) was prepared via a facile method. The introduction of binary Bi2 WO6 /MoS2 into g-C3 N4 could be qualified for constructing reasonable heterostructure while regulating photocatalysts morphology. Benefiting from the unique structure, the ternary heterojunction composites not only inhibited the agglomeration but also exhibited the prominent visible-light harvest capacity and abundant active sites, which could accelerate the photogenerated carriers separation and preserve the robust redox ability. The results showed that the optimized sample (CN-BM2) displayed the excellent degradation efficiency of sulfamethoxazole (SMX) under visible-light irradiation (over 99% within 60 min), and the fitted pseudo-first-order kinetic rate constant reached to 0.089 min −1, where it was 3.17 times than that of pure CN. Additionally, the radical scavenger experiments and electron spin resonance experiments indicated that the active species super-oxide radical and hole played a major role in the degradation experiment. The charge transfer mechanism was proposed and the main intermediates indicated that the active radicals attacked on the benzene ring and isoxazole ring in SMX, and further mineralized to inorganic molecules eventually. Graphical abstract: Image 1 Highlights: The introduction of BM regulated the morphology and constructed heterojunction. The hollow porous loofah-sponge-like structure enhanced the optical utilization. Ternary heterojunction exhibited effective carriers separation and transfer. SMX was rapidly removed by CN-BM under visible light irradiation. The mechanism and pathways of SMX degradation were proposed.